CHINA’S BELT AND ROAD INITIATIVE: BETWEEN GEOPOLITICS AND THE CORONAVIRUS CRISES - Azmukhanova А.M.; Malek, M. (Journal of Oriental Studies, 2022)
This paper examines the interests of China in the Belt and Road Initiative or BRI, framing these within the larger context of other participating and non-participating in BRI countries. Thus, the leading question is “where are the inevitable contradictions and incompatibilities of the interests of China and other countries?”, whereby the present analysis focuses on possible and probable environmental implications and consequences of BRI in the world. Consequently, parameters of BRI are considered from various angles to reveal prevalent views among specialists ranging from the belief in the determining effect BRI would have upon international relations to the views of inevitable abandonment of the project. Nevertheless, the authors of this paper argue that the project has important implications for the development of policies of the states involved in the BRI as well as for the research into international relations. Therefore, the paper concludes that BRI will deepen the already increasing dependencies of other states on China, the instances of which are most readily demonstrated during the coronavirus crisis in 2020 where the backdrop of the geopolitical fragility of the EU, China once again asserted its hegemonic role by lending out loans to economically vulnerable countries and supplying medical equipment to the rest of the world. As a result, there is no doubt that BRI will not reduce such dependencies, which is notably not the task of the project from Beijing’s perspective, but rather, they will become even more severe. Key words: BRI, initiative, China, European Union, Central Asia, national interest, challenges, risks, opportunities.